Identification of Relict Landslide Parts Based on Morphometric Data to Determine Potential Hazard Zones Combined with Surface Morphodynamics - R. Ramlah; Redo Saputro (Department of Geography Education, University of Jember, 2024)
The destruction of houses and facilities by landslide causes deaths. In this context, the level of destruction and subjective description of the characteristics can be examined through landslide parts determination. Therefore, this study aims to determine potential landslide hazard zone and houses potentially affected. Global Navigation Satellite System (GNSS) and unmanned aerial vehicle (UAV) are morphometric surveys combined with surface morphodynamics to show potential hazard zones of landslide parts. Meanwhile, Data Elevation Model (DEM) is used to delineate relict landslide and the concept is verified by field observation and orthophoto. Morphometric measurements are collected at each slope gradient by GNSS and surface morphodynamics are investigated on the entire relict landslide area by direct observation and orthophoto data. The combination of morphometric and morphodynamic data describes hazard zone of relict landslide. In addition, the integration of orthophoto and landslide hazard zone data is used to determine potentially affected houses. This study was conducted on landslides 1 and 2 with zone classifications of very high, high, low and very low. The results show that there are different conditions and the most hazardous parts of landslides 1 and 2 are the foot and body, respectively. A total of 75 and 50 houses were potentially affected by landslides 1 and 2, respectively. Identification of hazard zones based on landslide parts determines the boundaries of the area affected. The addition of surface activity processes determines the level of hazard in each of parts, while the combination of morphometric and morphodynamic data shows landslide zone.